Applications of the theory of generalized Fourier transforms to Tikhonov problems - Fethi Soltani; Akram Nemri (Journal of Numerical Analysis and Approximation Theory)
We define and study multiplier operators associated with the Sturm-Liouville operator involving a nonnegative function satisfying certain conditions. We introduce and study the extremal function, and we deduce approximate inversion formulas for the multipliers operators in a Paley-Wiener type space.